Improvement of soil moisture storage in clove plantation land using biopore technology and organic material litters - Buhari Umasugi; Sugeng Prijono; S Soemarno; A Ariffin (Journal of Degraded and Mining Lands Management, 2021)
The biopore infiltration hole with organic material litter can increase the soil capacity to accommodate and store soil moisture. This study was aimed to determine the effect of biopores and organic material litter on soil moisture storage and the relationship of climatic conditions on soil moisture storage. The experiment was carried out on clove plantations on Ternate Island, North Maluku from December 2018 to February 2019. This study used a factorial randomized block design. The first factor was the biopores with a depth of 50 cm and 90 cm, and the second factor was 4 types of organic material litters in the form of nutmeg leaves, clove leaves, Guinea grass leaves and a mixture of clove leaves and Guinea grass. The factors observed were total soil water storage and at depths of 0-20, 20-40, 40-60 and 60-80 cm; organic matter content; C/N ratio and soil total N. Data analysis used the GenStat program with analysis of variance test (ANOVA) and Duncan's Multiple Distance Test. Results of the study showed that evaporation and percolation are climatic factors that affect water loss. Increase in soil water storage at 20-40 cm soil depth of 107.56 mm was yielded by the treatment of 50 cm biopore and Guinea grass leaf litter but it was not significantly different from the 50 cm biopore and clove leaf litter + chicken manure treatment. The treatment of biopore and organic material litter also increased the organic matter and soil total N and decreased the soil C/N ratio, but it did not have a significant effect.